2020
DOI: 10.1080/09712119.2020.1776715
|View full text |Cite
|
Sign up to set email alerts
|

Development of local calibrations for the nutritional evaluation of fish meal and meat & bone meal by using near-infrared reflectance spectroscopy

Abstract: Fish meal and meat & bone meal from avian sources are the available animal protein sources mostly used in Bangladesh while formulating poultry diet. Due to the strong link between feed and food, the quality and safety of animal originated feed protein materials are the crucial public concern. The aim of this study was to explore the nutritional evaluation of fish meal and meat & bone meal by using near-infrared reflectance spectroscopy (NIRS). Samples were collected from different locations and feed mills in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The spectral information of meat was sensitive to the molecular bonds in meat, such as C-H, O-H, S-H, and N-H, which related to various quality attributes. The vibration overtones and vibration combinations of the above molecular bonds are related to the absorption peaks of the spectra ( Khaleduzzaman and Salim, 2020 ), and four significant absorption peaks at about 430 nm, 550 nm, 760 nm, and 980 nm wavelengths were shown in Fig. 4A .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spectral information of meat was sensitive to the molecular bonds in meat, such as C-H, O-H, S-H, and N-H, which related to various quality attributes. The vibration overtones and vibration combinations of the above molecular bonds are related to the absorption peaks of the spectra ( Khaleduzzaman and Salim, 2020 ), and four significant absorption peaks at about 430 nm, 550 nm, 760 nm, and 980 nm wavelengths were shown in Fig. 4A .…”
Section: Resultsmentioning
confidence: 99%
“…The 550 nm absorption peak also occurred in the visible region is mainly connected with the myoglobin in meat, and the absorption peak at 760 nm is connected with the deoxymyoglobin, which was produced by the O-H stretching third overtone involved in the pH, color, protein, moisture, and fat components. The absorption peak at 980 nm is related to O-H third stretch overtone, which is mainly related to the moisture content ( Khaleduzzaman and Salim, 2020 ). Due to the shear force being a physical parameter, which was formed by much more factors, its characteristic peak was difficult to find for relating some single corresponding groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Number of the articles published in this area between 1930 and 1940 was only 3, while this number were more than 1000 between 1980-1990(Egesel and Kahriman, 2012, and climbed over 15000 in 1998 (Pasquini, 2003). In Bangladesh, NIR spectroscopy studies related to animal feed are very scanty (Khaleduzzaman and Salim, 2020), and no information is available on the historical progress. As evident by the google search, domestic studies in this area are rather negligible; and no report has been found on the grain quality of maize.…”
Section: Introductionmentioning
confidence: 99%
“…28 The accuracy of the technique in measuring macronutrients in food has been already demonstrated by several studies. [28][29][30][31] Following the standardization procedures described by ISO 12099:2010 and ISO 21543:2006, food companies, analytical laboratories have switched from expensive and time-consuming wet chemistry to (NIR) spectroscopy to measure nutrient content.…”
Section: Introductionmentioning
confidence: 99%